Effects of the sintering temperature on structural and mechanical properties in Sr-Doped YSZ/HA bioceramics - Inthong S. (American Scientific Publishers, 2015)
Copyright © 2015 American Scientific Publishers All rights reserved. In this research, the effects of sintering temperatures on structural and mechanical properties in Sr-doped YSZ/HA ceramics were investigated. The Sr-doped YSZ/HA ceramics were fabricated under various sintering temperature in range 1000-1400°C. X-ray diffraction (XRD) technique and the scanning electron microscopy (SEM) are used to characterize phase and microstructure. The mechanical properties of the studied samples were determined by micro-hardness tester. The grain growth model was used for explanation the relation between grain size and sintering temperature by computation method. The sintering temperature is most influence in microstructure and mechanical properties. The highest density of studied ceramics was found at 1400°C. This result was related to the crystallinity. In this sintering temperature, the studied ceramics has shown the highest crystallinity. The microstructural properties of the studies samples were investigated and the results were then correlated with the characteristics of sintering temperature as well as the microstructure of the bioceramic.